ON THE RESOURCES OF DEMERSAL FISHES FOR BOTTOM TRAWLING IN INSHORE WATERS OFF KAKINADA BY SMALL MECHANISED BOATS - NARAYANAPPA, G; SREEKRISHNA, Y; SADANANDAN, K A (Fishery Technology, 2017)
An attempt is made to assess the available resources of demersal fishes for bottom trawling off Kakinada, in inshore waters. From the experimental fishing operation during 1964-66, the average catch per hour was 52.79 kg. for 9.13 m. (30’) OAL mechanised boat. The catch composition was dominated by prawns and sciaenids forming 45% of the total catch. The average catch per trawling hour was more during the quarter April - June. An assessment on the productive depth range has indicated that the catch rate is increasing with increase in the depth of fishing.